Lip Reduction Plasty: A Case Report and Review of Literature - Ozinko, MBA O.; Otei, Otei O.; Isiwele, Egi; Ekpo, Rijami G. (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2020)
Lip reduction is a plastic surgery procedure that enhances facial appearance by reducing the volume of   lower, upper or both lips. This procedure finds its usefulness in the present day lip reduction plasty as a form of cosmetic surgery. We present a 28-year- old female who complained of broad lips with a portion of red (wet) vermilion exposed when the mouth was closed. We present this rare aesthetic surgical procedure in our hospital and also a search of relevant literature.